A World without Waste? - Docksai, Rick (Futurist)
The article discusses zero waste programs performed by communities, government agencies, and businesses in North America and Europe, where the goal is to recycle or reuse all waste products. Topics include the U.S. Army's Net Zero Waste 2020 initiative where they are striving to have close to zero waste output by the year 2020, the Zero Waste in Industrial Networks (ZeroWIN) initiative in Europe, and California Polytechnic State University's (Cal Poly) Global Waste Research Institute (GWRI).